1995
DOI: 10.1103/physrevc.52.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gogny-type interactions on the nuclear flow

Abstract: A flow analysis on symmetric and asymmetric reactions from 100 to 400 MeV/nucleon is performed in the framework of the semiclassical Landau-Vlasov approach. In this energy range our results present two different trends. At lower energies it is governed by the momentum dependence of the nuclear optical potential, whereas at higher energies its density dependence plays a crucial role leading to a rather pronounced sensitivity to the incompressibility modulus. The nonlocality of the nuclear interaction is relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The original Gogny force 15) has a soft EOS with the incompressibility K = 228 MeV. Recently, Haddad et al have made a stiff version of Gogny force (D1-G3) 25) which has a large incompressibility of K = 360 MeV. They applied this force to the study of collective flow in heavy ion collisions.…”
Section: A Onomentioning
confidence: 97%
“…The original Gogny force 15) has a soft EOS with the incompressibility K = 228 MeV. Recently, Haddad et al have made a stiff version of Gogny force (D1-G3) 25) which has a large incompressibility of K = 360 MeV. They applied this force to the study of collective flow in heavy ion collisions.…”
Section: A Onomentioning
confidence: 97%
“…In this case, the in-medium nucleon-nucleon total cross section reads: 10) where the nucleon effective mass m * is defined as: and we have replaced the r dependence in u with a ρ dependence which is appropriate for an equilibrium nuclear matter distribution. Note that the density ρ( r ) is a constant in this case and it enters into the above relation selfconsistently via the semi-classical phase space distribution function f (see, for example, Ref.…”
Section: B In-medium Effects In Nucleon Collisionsmentioning
confidence: 99%
“…In connection with observables, a considerable amount of information on the nuclear equation of state and on nonequilibrium precursor phenomena is accessible through the measurement of global collective behaviour. A large body of work in intermediate energy nuclear collisions has been devoted to the measurement and to the theoretical calculation of both directed flow [7][8][9][10], and elliptic flow [11][12][13][14][15]. For a review, see [16].…”
Section: Introductionmentioning
confidence: 99%
“…The parametrization of Equation 6 neglects the momentum dependence of the real part of the optical nucleon-nucleus potential which is known to become repulsive around 300 MeV and converges toward 30 MeV for very high nucleon momenta. The effect of the momentum dependence of U (ρ, p) was first studied by Gale, Bertsch, and DasGupta (86) and by Aichelin (87) using phenomenological Ansätze and was further developed by Welke et al (88) and Haddad et al (89). It was found that an equation of state with an incompressibility of about 215 MeV and a reasonable U (ρ, p) could fit then-available data as well as a stiff equation of state without momentum dependence.…”
mentioning
confidence: 99%